A ANALISIS BAURAN PEMASARAN DALAM MINAT BELI PRODUK IGOOD COFFEE - Subarkah, Rahmat; Rustam, Kuswadi; Halimah, Nur (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2024)
The level of competition in the world of marketing is very tight, making every company always try to be able to increase market share and reach new consumers. Companies must be able to determine the right marketing strategy. Igood Coffee is one of the MSMEs in Purworejo Regency who has just started his business and needs a marketing strategy to boost product sales. This research was conducted to find out more about the effect of the marketing mix (product, price, promotion, and place) on purchasing decisions for Igood Coffee products, either partially or simultaneously. The approach was carried out using a simple random sampling method to take 42 respondents as a sample. In the instrument test using validity and reliability tests. Data analysis technique using multiple linear regression. The results showed that the product variables and place variables had a positive and significant effect on purchasing decisions for Igood Coffee products, while price variables and promotion variables did not have a significant effect on purchasing decisions. Based on the test results it is also known that simultaneously there is a positive and significant influence between the marketing mix (product, price, promotion, and place) on purchasing decisions for Igood Coffee products. Therefore, Igood Coffee must pay attention to pricing and promotion by optimizing social media. In addition, Igood Coffee must maintain product quality and offer good service facilities to influence purchasing decisions and interest in buying Igood Coffee products.